MANAJEMEN PEMBELAJARAN BERBASIS STANDAR PROSES DI TAMAN KANAK-KANAK (TK) - Mustofa; Suqya Rahmah; Teti Ratnawulan; Lilis Suwandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is motivated by a gap between the PAUD Process Standards and actual practice at TK Darul Uchwah, Jakarta—particularly the readiness of RPPM/RPPH documents, a tendency toward cognitive emphasis, and limited facilities. The study aims to describe and analyze Process-Standards–based instructional management through the POAC functions. A qualitative–descriptive approach was used with interviews, observations, and document analysis; participants included the principal, teachers, and children. The theoretical framework refers to G.R. Terry’s POAC and Mulyasa’s instructional management. Findings include: (1) planning is tiered from the academic calendar–Prota–Promes–CP/ATP to RPPM/RPPH, internally verified, flexible in classroom use, and integrates STPPA and value reinforcement; (2) organizing clarifies the principal’s role as in-class mentor and teachers as daily managers, arranges learning centers and manipulatives, and groups children by age with in-class differentiation; (3) actuating follows an opening–core–closing sequence, applies a simplified scientific approach, provides choice of activities, documents processes and products via checklists/worksheets and anecdotal records, and blends visual and concrete media; (4) controlling includes device verification, semesterly supervision, ongoing authentic assessment, physical monitoring, and daily–semester follow-up. The study concludes that Process-Standards–based instructional management at TK Darul Uchwah operates effectively and aligns with POAC, though challenges remain regarding attendance and facilities. This implementation can serve as a reference for continuous improvement in other PAUD settings through strengthened planning SOPs, robust documentation of authentic assessment, parent partnerships, and phased facility development.